Is it them or is it us? Unravelling ethnic disparities in undergraduate clinical performance - Karen M. Stegers-Jager (BMC Medicine, 2017)
Abstract Given our increasingly diverse societies, there is an urgent need for research into the causes of persistent ethnic disparities in undergraduate clinical performance. It is argued that causes for underperformance can be identified from two perspectives, namely that of the students (‘them’) and that of the academic environment (‘us’). Taking the ‘us’ perspective, Yeates et al. conducted a detailed experimental study aimed at understanding the processes underlying judgment and decision-making in clinical assessments. Contrary to their expectations, their study indicates that, despite the presence of active stereotypes, examiner bias does not explain ethnic minority students’ underperformance. Naturally, future studies are required to confirm their findings. It is suggested that these studies should take into account various rater and situational factors (e.g. rater experience, increased cognitive load) that may influence examiners’ reliance on stereotypes. However, future work should also focus on other potential impeding factors from both perspectives, including differences in communication styles. Knowing what leads to the ethnic disparities in performance is a prerequisite for designing interventions aimed at ensuring a level playing field for a diverse student population. Please see related article: https://bmcmedicine.biomedcentral.com/articles/10.1186/s12916-017-0943-0